Mechanical properties of new endodontic instruments: a comparative approach with different in vitro tests - Maya Feghali; Biraj Patel; Dina Adami; James Wealleans; Massimo Galli; Tugba Turk (Annali di Stomatologia)
The goal of the present study to tested and compared a new file system (“Diamond“, Edge Endo, Albuquerque, NM) with a well-known and investigated one (Protaper Gold, Dentsply Maillefer, Baillegues, Switzerland) using three of the most widely used testing methods for NiTi rotary instruments : stiffness, torsional and cyclic fatigue tests. For each size and test, ten instruments were analyzed for each of the two brands and then the data were collected. Mean values and the standard deviations of all tests were then statistically analyzed using 1-way ANOVA followed by the post hoc Tukey test with significance set to a 95% confidence level. Results from the present study showed that the new “Diamond” instruments are more flexible than Protaper in size 25 (F2). On the contrary Protaper size 25 is more resistant to torsional stress when measuring torque at failure. All the other sizes show no statistically significant difference it the previously mentioned tests. On the contrary, statistically significant differences can be noted in all sized when evaluation torsional resistance using the deflection angle and cyclic fatigue, with “Diamond” instruments providing the best Results. Therefore, data of the present study suggest the clinical use of the new “Diamond “ instruments for easy, safe and predictable root canal shaping procedures